NFAT5‐sensitive Orai1 expression and store‐operated Ca2+ entry in megakaryocytes. Issue 8 (19th September 2017) - Sahu, Itishri; Pelzl, Lisann; Sukkar, Basma; Fakhri, Hajar; al‐Maghout, Tamer; Cao, Hang; Hauser, Stefan; Gutti, Ravi; Gawaz, Meinrad; Lang, Florian
ABSTRACT: The transcription factor nuclear factor of activated T cells 5 (NFAT5) is up‐regulated in several clinical disorders, including dehydration. NFAT5‐sensitive genes include serum and glucocorticoid‐inducible kinase 1 (SGK1). The kinase is a powerful regulator of Orai1, a Ca 2+ channel accomplishing store‐operated Ca 2+ entry (SOCE). Orai1 is stimulated after intracellular store depletion by the Ca 2+ sensors stromal interaction molecule 1 (STIM1), or STIM2, or both. In the present study, we explored whether nuclear factor of activated T cell (NFAT)‐5 influences Ca 2+ signaling in megakaryocytes. To this end, human megakaryocytic (MEG‐01) cells were transfected with NFAT5 or with siNFAT5. Platelets and megakaryocytes were isolated from wild‐type mice with either access to water ad libitum or dehydration by 36 h of water deprivation. Transcript levels were determined with quantitative RT‐PCR and protein abundance by Western blot analysis and flow cytometry, cytosolic (intracellular) Ca 2+ concentration ([Ca 2+ ]i ) by fura‐2‐fluorescence. SOCE was estimated from the increase of [Ca 2+ ]i following readdition of extracellular Ca 2+ after store depletion with thapsigargin (1 mM). Platelet degranulation was estimated from P‐selectin abundance and integrin activation from αIIb b3 integrin abundance determined by flow cytometry. As a result, NFAT5 transfection or exposure to hypertonicity (+40 mM NaCl) of MEG‐01 cells increased Orai1, Orai2, STIM1, and STIM2 transcript levels. Orai1 transcript levels were decreased by NFAT5 silencing. NFAT5 transfection and IkB inhibitor BMS 345541 (5 mM) increased SOCE, whereas NFAT5 silencing and SGK1 inhibitor GSK650394 (10 mM) decreased SOCE. In the mice, dehydration increased NFAT5 and Orai1 protein abundance in megakaryocytes and NFAT5, Orai1, and Orai2 abundance in platelets. Dehydration further augmented the degranulation and integrin activation by thrombin and collagen‐related peptide. In summary, NFAT5 is a powerful regulator of Orai1‐expression and SOCE in megakaryocytes.—Sahu, I., Pelzl, L., Sukkar, B., Fakhri, H., al‐Maghout, T., Cao, H., Hauser, S., Gutti, R., Gawaz, M., Lang, F. NFAT5‐sensitive Orai1 expression and store‐operated Ca 2+ entry in megakaryocytes. FASEB J . 31, 3439–3448 (2017). www.fasebj.org